Analysis of Education Financing Concepts and Tax Systems - Muhammad Saripuddin B (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this writer is to discuss about. 1) Knowing education financing and, 2) taxation in education. This type of research is Library Studies research, which in this study will take various expert opinions and analyze from various theories regarding education financing and taxation. The conclusion of this paper is the concept of education financing according to Thomas John, among other things, namely 1) how money is obtained to finance educational institutions, 2) where does it come from, 3) and what is it spent on and who spends it, then the income or source of education funds received by the school is obtained from the State Revenue and Expenditure Budget, Regional Revenue and Expenditure Budget, and the community or parents. As for the use of these funds, each school should establish plans that are a priority for comprehensive education financing. As for the taxation system in improving the quality of education in Indonesia, it has consistently allocated the State Budget for the Education Budget by 20% of the State Budget, with a focus on increasing access and quality of education services that are equitable in all regions to all corners of the country either through direct allocations in the State Budget or transferred to regions through budget allocations. in the APBD of each region by prioritizing improving the quality of students compared to capital expenditure. The taxation system also requires educational institutions as corporate income tax subjects to: 1) Register at the Directorate General of Taxation to be recorded as taxpayers and obtain a taxpayer identification number (NPWP), 2). Calculating and reporting tax payable (PPh articles 25 and 29), 3). Withholding and collecting tax payable (PPh articles 21, 22 and 23)